Amateur content production, networked innovation and innovation policy - Quiggin John (Cultural Science)
The central common feature of a number of recent technological developments (collectively referred to as Web 2.0) is collaborative production of content on an amateur basis, that is, for motives other than commercial reward. Amateur production of content generates significant external benefits that are shared by society in general. Indeed the amateur production of various types of content is probably more socially beneficial since it is typically given away free The individual and social benefits of such activity therefore justify public policy responses to the opportunity now before us.